How caregivers of people with dementia search for dementia-specific information on the internet: Survey study - Efthymiou, Areti; Papastavrou, Evridiki; Middleton, Nicos; Markatou, Artemis; Sakka, Paraskevi (My University, 2020)
Background: During the last decade, more research has focused on web-based interventions delivered to support caregivers of people with dementia. However, little information is available in relation to internet use among caregivers in general, especially those caring for people with dementia. Objective: The aim of this study was to evaluate the dementia-related internet use and factors that may be associated with its use among caregivers of people with dementia in Greece. Methods: Secondary data from the Greek Dementia Survey of the Athens Association of Alzheimer's Disease and Related Disorders were collected from April to June 2017. A total of 580 caregivers of people with dementia participated in the study. Results: The majority of the caregivers reported that they had used the internet in the previous 3 months (84.1%, 488/580). Nearly half of the caregivers (47.5%, 276/580) reported that they had received dementia services online. Bivariate analysis showed that a dementia-specific search of information was associated with age, education, kinship, and years of care. Age (odds ratio [OR] 2.362, 95% CI 1.05-5.33) and education (OR 2.228, 95% CI 1.01-4.94) were confirmed as predictors, with younger caregivers and those with higher educational attainment being more likely to search for dementia-specific information. Use of the internet to search for dementia information was only related to hours of care. The internet use by caregivers within the previous 3 months was associated with variables such as age, education, occupation, kinship, years of care, and self-reported impact on physical and social health. Conclusions: Caregivers of people with dementia in Greece, as in the other southern European countries, are essential agents of the national health system. The existing short- and long-term respite care services are limited or nonexistent. Currently, caregivers receive mostly support and education from memory clinics and municipality consultation centers, which are mainly based in central cities in Greece. Despite the dementia awareness movement in Greece, there is still space to integrate the role of technology in the support and education of caregivers. Development of training programs for enhancing electronic health literacy skills as well as web-based services provision could support Greek caregivers in their everyday caring tasks.
Keywords: Caregivers; Dementia; EHealth; Internet